PENGARUH SIKAP PROFESIONALISME, PENGALAMAN, DAN KECERDASAN INTELEKTUAL TERHADAP PERTIMBANGAN TINGKAT MATERIALITAS - Marsyaf Marsyaf (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2017)
This study aims to analyze the influence of professionalism attitude, experience, and intellectual intelligence on the consideration of the level of materiality both simultaneously and persially. Independent variables used in this study is the attitude of professionalism, experience and intellectual acumen. While the dependent variable in this study is the consideration of the level of materiality.This study used survey method, collected at 9 Public Accounting Firm in South Jakarta area. Data were collected by spreading the questionnaire with convenience sampling method. There are 80 questionnaires distributed, 71 returned and 71 questionnaires that can be analyzed. Data processing was done by using validity test, reliability, classical assumption test and multiple linear regression test with Statistical Product and Service Solution (SPSS) version 21 and Microsoft Excel 2007. The results of this study indicate that the attitude of professionalism partially affect the consideration of materiality, experience does not affect the materialial level of materiality, and intellectual intelligence does not affect the level of materiality.